2005
DOI: 10.1038/sj.ijo.0803086
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low carbohydrate on energy metabolism

Abstract: OBJECTIVE: To investigate whether low-carbohydrate diets are efficient for reduction of body weight and through which mechanism. DESIGN: A couple of studies using low-carbohydrate diets in the treatment of obesity are reviewed. Mechanisms for explaining the reduced appetite are described in relation to knowledge on regulation of appetite for fat and carbohydrate. RESULTS: Studies with low-carbohydrate diets demonstrate a rapid weight loss, being more pronounced after 3 and 6 months compared to low-fat diets. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…Later, weight loss is more difficult to explain. Some authors have suggested that ketones act on the satiety center of the brain and suppress hunger [13], while others believe that it is simply the physical form of the carbohydrate consumed that affects satiety [33]. Increased lipolysis (due to reduced insulin secretion) does promote weight loss [43], but probably not to a significant extent.…”
Section: Weight Loss Mechanisms In Ketogenic Dietsmentioning
confidence: 98%
“…Later, weight loss is more difficult to explain. Some authors have suggested that ketones act on the satiety center of the brain and suppress hunger [13], while others believe that it is simply the physical form of the carbohydrate consumed that affects satiety [33]. Increased lipolysis (due to reduced insulin secretion) does promote weight loss [43], but probably not to a significant extent.…”
Section: Weight Loss Mechanisms In Ketogenic Dietsmentioning
confidence: 98%
“…There are evidences that the low-carbohydrate diet results in quick weight loss because of enhanced energy expenditure via ketogenesis [29], or simply by appetite suppression due to high protein content [30]. Researchers believe that this weight loss occurs because of the combination of limited food choice with the satiety promoted by the large amount of protein in the diet [14].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that energy metabolism is changed with a low-carbohydrate diet, leading to decreased body weight, mainly because of increased satiety from fat and protein and an increased thermogenesis. 45 Psychology Psychological aspects are important in both the development and the treatment of childhood obesity. We have to use the encounter with the patient as professionally as possible as this is a major tool in treatment.…”
Section: Metabolismmentioning
confidence: 99%